Estimation of aortic pulse pressure using fourier velocity encoded M‐mode MR. Issue 1 (7th November 2013) - Taviani, Valentina; Hickson, Stacey S.; Hardy, Christopher J.; Patterson, Andrew J.; Young, Victoria E.; McEniery, Carmel M.; Wilkinson, Ian B.; Gillard, Jonathan H.; Graves, Martin J.
Abstract : Purpose: To use a simplified hemodynamic model and Fourier‐encoded velocity data to measure pulse pressure (PP) in the descending aorta. Materials and Methods: A one‐dimensional, cylindrically localized pulse sequence with Fourier velocity encoding (FVE) was used to obtain time‐dependent velocity distributions along the descending aorta. Numerical evaluation of a simplified hemodynamic model, based on a cross‐sectionally averaged form of the mass conservation equation, allowed estimation of the average pressure waveform and PP along 6‐cm‐long segments located within the descending aorta. Magnetic resonance (MR)‐derived pressures were compared against applanation tonometry (AT) performed in healthy subjects ( n = 18) and intravascular pressure measurements (IVPM) obtained in patients ( n = 4) undergoing diagnostic cardiac angiography and then found to be either normal or with clinically insignificant coronary artery disease. Results: The root mean square (RMS) error between MR‐ and AP‐derived pressure waveforms was 11.7 ± 5.8%. With respect to IVPM, the RMS error ranged from 4.2% to 14.7%. In terms of pulse pressures, there was good agreement with both AT (bias = 0.99 mmHg; 95% limits of agreement (LOA) = [−5.0 to 7.0 mmHg]; range = 12.0 mmHg) and IVPM (bias = −1.82 mmHg; 95% LOA = [−7.2 to 3.5 mmHg]; range = 10.7 mmHg). Conclusion: FVE M‐mode and numerical evaluation of a simplified flow model can be used to estimate central pulse pressures noninvasively and accurately with respect to well‐established gold standards. J. Magn. Reson. Imaging 2014;39:85–93. © 2013 Wiley Periodicals, Inc.